Evaluation of winged beans (Psophocarpus tetragonolobus) as an aquafeed ingredient on growth and enzymatic activity of java barb fish (Barbonymus gonionotus) - Santika Dewi Astuti; Setya Arum Maulidina; Andri Nofreeana; Shobrina Silmi Qori Tartila (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2024)
This study evaluated the heated winged beans as a plant-based aquafeed ingredient on growth and enzymatic activity in Java barb fish. This study had four treatments and four replications using the CRD method. Treatments contained heated winged beans in an oven at 110°C for 30 minutes (KO) and an autoclave at 121°C for 30 minutes (KA), non-heated winged beans (KE), and feed without winged beans administration (K). Specific growth rate/SGR, weight gain/WG, feed intake/FI, protein retention/PR, and lipid retention/LR were analyzed using one-way ANOVA, followed by DMRT. The protease enzyme activity (U/ml) of Java barb fish was analyzed descriptively. The SGR and WG had insignificant differences among treatments (p>0.05). In LR and PR, the best value was obtained in KO (82.89±0.96 and 95.67 ± 2.73%). The JKP in KO (107.83 ± 5,24 g) had a higher value than K (64.5 ± 8,19 g, p